1991
DOI: 10.1073/pnas.88.2.487
|View full text |Cite
|
Sign up to set email alerts
|

2-nitro-3-(p-hydroxyphenyl)propionate and aci-1-nitro-2-(p-hydroxyphenyl)ethane, two intermediates in the biosynthesis of the cyanogenic glucoside dhurrin in Sorghum bicolor (L.) Moench.

Abstract: The biosynthetic pathway for the cyanogenic glucoside dhurrin derived from tyrosine has been studied in vitro by using ['80]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The current study advances our mechanistic understanding of the reactions catalyzed by CYP79A1 and CYP71E1 with respect to the structure of geometrical isomer of the p-hydroxyphenylacetaldoxime produced. In previous studies, it was demonstrated by radiolabeling experiments that the dhurrin pathway included both the E and Z geometrical oxime isomers as obligatory intermediates and that E-oxime was produced first and subsequently converted into the Z-oxime isomer (Halkier et al, 1991). However, in studies using isolated CYP79A1 reconstituted in liposomes, E-as well as Z-oxime were observed as products (Halkier et al, 1989(Halkier et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study advances our mechanistic understanding of the reactions catalyzed by CYP79A1 and CYP71E1 with respect to the structure of geometrical isomer of the p-hydroxyphenylacetaldoxime produced. In previous studies, it was demonstrated by radiolabeling experiments that the dhurrin pathway included both the E and Z geometrical oxime isomers as obligatory intermediates and that E-oxime was produced first and subsequently converted into the Z-oxime isomer (Halkier et al, 1991). However, in studies using isolated CYP79A1 reconstituted in liposomes, E-as well as Z-oxime were observed as products (Halkier et al, 1989(Halkier et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was demonstrated by radiolabeling experiments that the dhurrin pathway included both the E and Z geometrical oxime isomers as obligatory intermediates and that E-oxime was produced first and subsequently converted into the Z-oxime isomer (Halkier et al, 1991). However, in studies using isolated CYP79A1 reconstituted in liposomes, E-as well as Z-oxime were observed as products (Halkier et al, 1989(Halkier et al, , 1991. In the present study, improved technologies and faster experimental conditions enabled us to demonstrate that the CYP79A1 enzyme specifically produces the E structural isomer, although a minute amount of the Z structural isomer was always detected (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of the biosynthesis of cyanogenic glycosides, in vitro experiments in which microsomal enzyme preparations are used have contributed greatly to the characterization of the intermediates involved (Mdler and Conn, 1979;Halkier and Mdler, 1989;Halkier et al, 1989Halkier et al, , 1991Conn, 1991). In view of this, it would obviously be desirable to obtain a similar microsomal enzyme system catalyzing the biosynthesis of glucosinolates.…”
mentioning
confidence: 99%